Optimal power system operation and planning of investments in new lines, energy storage and continuous serial compensation of power lines : doctoral thesis - Luburić, Zora (Z. Luburić, Faculty of electrical engineering and computing, 2021)
Modern power systems tend to increase the capacity of integrated RES. While the RES contribute to power system decarbonisation, on the other hand their variable generation is often characterized as poorly predictable and controllable, often away from the load centres. Transmission of electricity in periods of high production might cause line congestion. However, there are devices that can improve efficiency of electricity transmission and provide flexibility to the grid, such as Energy Storage (ES) and Flexible Alternating Current Transmission Systems (FACTS) devices considering Thyristor-Controlled Series Capacitor (TCSC) devices. This thesis deals with ES performing energy arbitrage and deferring transmission investment, while FACTS devices also defer investment by changing the line impedance thus reducing the line congestion. The first part of the thesis is based on operational models in transmission power systems with increased share of non-controllable renewable generation using direct- (DC) and alternating- current (AC) network models. Impact of the two technologies, i.e. ES and FACTS, on power system flexibility and security is exhaustively researched. The second part of the thesis presents Transmission Expansion Planning (TEP), which is developed considering new lines, ES and series compensation of power lines using AC network model of power flows. The TEP problem is solved using Benders decomposition. Since TCSC devices focus only on the reactive power component, the ES has the ability to control both the operating and reactive power components. In addition, two new items have been proposed. First, a dynamic TCSC device is modeled whereby the compensation value is actively adjusted in each time unit between zero and the installed compensation capacity. Second, the ES is modelled, not only for the purpose of injecting or taking active power by discharging or charging the battery, which is common in the literature but its AC-DC converter is also used to inject or take reactive power with a tendency to regulate the voltage. The most relevant conclusions of the thesis are: ES is more efficient in reducing system operating costs than FACTS devices, while the wind curtailment is effectively reduced by both technologies. However, the effectiveness of energy storage of reducing system operating costs and wind curtailment significantly depends on the wind profile. The current prices of ES and FACTS are still quite high, making the investment in new lines still the most attractive option. However, for lower ES costs, ES is installed at multiple buses, reducing the wind curtailment, but also taking part in voltage control. Investment in FACTS is less attractive and yields lower returns than the investment in new lines. However, it also complements the ES and can come handy at locations where installation of new lines is not possible.